Impact of inflation severity on retirement savings: A simulation analysis of projected accumulation and de-accumulation - Foziah, Hazimi; Afthanorhan, Asyraf; Ghazali, Puspa Liza; Tajuddin, Sheikh Ahmad Faiz Sheikh (Journal of Social Economics Research, 2023)
Statistics have shown that by the age of 60, Malaysian life expectancy for males and females is expected to be 17.5 and 20.1 years, respectively. Thus, if not properly addressed by the authorities, the ageing population would contribute to a serious problem for the public by having an inadequacy of retirement wealth to sustain their lives. Considering all of these issues, the present study seeks to comprehensively examine the extent to which inflation adversely affects retirement savings. This investigation holds the potential to yield valuable insights into the accumulation of retirement wealth, thereby addressing the issue of insufficient retirement income, particularly among members of the Employees Provident Fund. Using a mathematical iteration formulation approach, the accumulation and de-accumulation of retirement wealth subject to inflation are formulated to examine the severe impact of this economic factor. Ironically, the disruptive effect of inflation on retirement savings is not severe. It is the power of compounding returns generated by dividend profits that absorbs the real impact. Despite the fact that this is a useful insight, people must plan well for their retirement savings to avoid having them eaten up by inflation. The results showed that inflation disruptions of varying degrees can negatively impact retirement funds. In order to effectively mitigate the potentially detrimental impact of inflation on retirement savings, it becomes imperative to adopt a strategic approach that encompasses various measures, like the exploration of investment opportunities that possess the potential to generate returns surpassing the prevailing inflation rate.